2008
DOI: 10.1037/0021-9010.93.5.1130
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of coworker trust: Leaders' blessings.

Abstract: Although employee trust in leaders has garnered substantial empirical research, trust between coworkers has been virtually ignored. Extending the work of D. L. Ferrin, K. T. Dirks, and P. P. Shah (2006), the authors examined the role of group leaders, an influential third party in the workplace, on coworker trust formation. The correlates of the extent to which coworkers trust one another were examined in an investigation of 146 members of 32 work groups representing 4 diverse organizations. In this study, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
196
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(204 citation statements)
references
References 81 publications
6
196
0
2
Order By: Relevance
“…The idea that coworker helping behaviors targeted at coworkers can impact downstream trust and perceived support and are reciprocated in the form of helping behavior back toward a coworker suggests that helping behavior should be formally and informally encouraged and rewarded (Lau & Liden, 2008). While this may seem a rather superficial suggestion, we recognize that many organizations pay lip service to the benefits of helping behavior among coworkers while at the same time using reward systems that reward individual behavior.…”
Section: Implications For Practicementioning
confidence: 98%
See 2 more Smart Citations
“…The idea that coworker helping behaviors targeted at coworkers can impact downstream trust and perceived support and are reciprocated in the form of helping behavior back toward a coworker suggests that helping behavior should be formally and informally encouraged and rewarded (Lau & Liden, 2008). While this may seem a rather superficial suggestion, we recognize that many organizations pay lip service to the benefits of helping behavior among coworkers while at the same time using reward systems that reward individual behavior.…”
Section: Implications For Practicementioning
confidence: 98%
“…Researchers have also highlighted the formal role of the supervisor in developing trust between coworkers (Bruk- Lee & Spector, 2006;Lau & Liden, 2008). Because interpersonal conflict in the workplace increases stress (Bruk-Lee & Spector, 2006), supervisors should have multiple motives to act as the first line of defense in mediating coworker conflict (Lau & Liden, 2008). The interaction between employees and supervisors relative to conflict, whether between coworkers or between employees and supervisors, is complex.…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…As a result, a multilevel theoretical model must be developed and tested to address how work group cultural context at individual level of analysis influences interactions between group members and work group outcomes at group level analysis (Hipp, Faris & Boessen, 2012;Lau & Liden, 2008;Lepine et al, 2008). Additionally, current explanatory theories and perspectives towards co-workers interaction and work diversity (e.g., leader-member exchange and team-member exchange theory)…”
Section: Introductionmentioning
confidence: 99%
“…However, trust can be transferred indirectly through observing a trusted third party's interactions with a trustee (Ferrin et al, 2006) or inferred from their unspoken but observable trusting behaviours (Coleman, 1990). For example, Lau and Liden (2008) found that co-workers tended to trust each other when the team leader also trusted that member. As such, a trusted third party provides a useful source for the trustee to leverage.…”
Section: Third Party Information -Trust Transferencementioning
confidence: 99%